Kewirausahaan dalam Perspektif Pendidikan Agama Kristen : Pendekatan Deskriptif terhadap Tantangan Masyarakat Modern - Liena Hulu,; Sumiati Titi,; Yosia Belo, (Student Scientific Creativity Journal, 2024)
Entrepreneurship is one of the main pillars of economic development in modern societies. However, the practice of entrepreneurship often faces complex ethical and moral challenges amidst the dynamics of globalization. This article aims to explore how the values of Christian religious education can provide a spiritual and ethical foundation in addressing these challenges. Using a qualitative descriptive approach, this research examines a range of relevant academic literature, including articles and books, to illustrate the potential integration between Christian religious education and entrepreneurial spirit development. The results show that values such as integrity, justice, responsibility and love can serve as moral guidelines for Christian entrepreneurs to face modern challenges without losing the essence of their faith. Christian religious education plays a role not only in shaping individual character, but also in creating entrepreneurs who have the vision to bring positive social impact. The findings emphasize the importance of a holistic approach in education that integrates spiritual values and entrepreneurial practices to create a more equitable and sustainable society. This research is expected to contribute to the development of a Christian values-based entrepreneurship education model, as well as a solution to the moral challenges in entrepreneurship in the modern era.